Evaluasi Lingkungan dan Situasi Ritel Modern dengan ImportancePerformance Analysis untuk Meningkatkan Niat Pembelian Ulang - Hanum Rachmawati Nur; Megawati Simanjuntak; Bagus Sartono (Faculty of Economics and Business Udayana University, 2020)
The focus of this study is to analyze the performance of modern retail toward the importance of modern retail based on the perspective of modern retail consumers. The use of the Importance-Performance Analysis (IPA) method is to measure the importance of modern retail attributes according to the perceptions of modern retail consumers. These researches were involved 244 respondents, randomly selected through online surveys. The results showed that there were no differences in consumer perceptions between the types of modern retail hypermarkets and supermarkets in general. The indicators that are the main priority for improvement sequentially are the unfavorable activities, price fairness with quality, the gentleness of employees, and quality assurance of the product. The indicators such as good quality of products, product variations, ease of product information search, spacious rooms, easy accessibility, availability of domestic products, affordable prices, and ease of obtaining low-priced products, have met customer expectations so the development in these aspects should be used for developing high importance attributes.